Present restrictions of sewage sludge application in agriculture within the European Union - Hudcová, Hana; Vymazal, Jan; Rozkošný, Miloš (Soil and water research, 2019)
The use of sludge in agriculture within the European Union (EU) is currently regulated only by the limits of heavy metals (Cd, Cu, Hg, Ni, Pb and Zn) listed in Council Directive 86/278/EEC. This document is now more than 30 years old. Several European countries have introduced more stringent requirements in comparison with the directive, and have adopted limits for concentrations of other heavy metals, synthetic organic compounds and microbial contamination. The paper provides an overview of the current limits of these substances in sewage sludge and concentration limits of heavy metals in soil intended for sludge application, together with applicable laws and regulations in European Union countries. There is a need to update these regulations taking into account the current risks associated with the application of sludge to agricultural land, with the possibility of using ecotoxicological tests to assess the risks. A wide range of technologies for sewage sludge processing is used in EU countries. The predominant choice is a direct application in agriculture followed by composting. The use of sewage sludge in agriculture in 2014 and 2015 in 13 EU countries that provided data amounted to 22.6% (2014) and 22.1% (2015) of produced sludge and 23.3% (2014) and 23.1% (2015) of sludge disposed. It is also highly variable within EU countries ranging between zero (Malta, Slovenia, Slovakia) and 80% (Ireland). Over 50% of sewage sludge is used in agriculture in Bulgaria according to 2015 data.